Microdosimetry with a sealed mini-TEPC and a silicon telescope at a clinical proton SOBP of CATANA. (June 2020) - Bianchi, A.; Selva, A.; Colautti, P.; Bortot, D.; Mazzucconi, D.; Pola, A.; Agosteo, S.; Petringa, G.; Cirrone, G.A.P.; Reniers, B.; Parisi, A.; Struelens, L.; et al.
Abstract: A sealed miniaturized Tissue Equivalent Proportional Counter (mini-TEPC) able to work in gas-steady modality was developed at the Legnaro National Laboratories of the Italian National Institute of Nuclear Physics (LNL – INFN, Legnaro, Italy). The aim of the present work is to compare the response of this mini-TEPC with that of a silicon microdosimeter based on a monolithic telescope. Pairwise measurements were performed at the 62 MeV proton clinical Spread Out Bragg Peak (SOBP) of CATANA at the Southern National Laboratories of INFN (LNS – INFN, Catania, Italy). The dose mean lineal energy values were derived from the spectra measured with the two detectors and compared with the total dose-averaged LET calculated by means of Geant4 Monte Carlo simulations. Finally, the possibility to apply the Microdosimetric Kinetic Model (MKM) to reproduce RBE variations with depth along the Spread Out Bragg Peak was investigated. Highlights: A new sealed mini-TEPC was tested as clinical monitor of radiation quality. Silicon telescope was used to enhance resolution in the distal part of SOBP. Dose mean lineal energy was evaluated as microdosimetric estimation of LETd . RBE was estimated using the MKM model, differences and similarities are discussed.